1995
DOI: 10.1177/039139889501800210
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Homozygous and Double Heterozygous Familial Hypercholesterolemia Children with LDL-Apheresis

Abstract: Within the framework of a seven-year clinical experience on treatment of severe hyperlipoproteinemia with/without associated coronary heart disease, with therapeutic plasmapheresis (APO B-100-containing lipoprotein-apheresis), we focused the present report on two young patients aged 7 and 11 years, respectively. The older patient is a boy treated since 1990 by plasma-exchange, cascade filtration-low density lipoprotein apheresis (LDL-apheresis), and dextrane sulphate-LDL apheresis. Over the treatment period th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…However, some symptoms such as shivering, nausea, vertigo (5) or a vasovagal reaction (10) suggested a reaction to bradykinin. Hypochromic anemia has been observed in some studies (4,10), but was not found in our children. The problems of hypovolemia and hypotension were present in the youngest children and could be easily treated by plasma expenders (8).…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…However, some symptoms such as shivering, nausea, vertigo (5) or a vasovagal reaction (10) suggested a reaction to bradykinin. Hypochromic anemia has been observed in some studies (4,10), but was not found in our children. The problems of hypovolemia and hypotension were present in the youngest children and could be easily treated by plasma expenders (8).…”
Section: Discussioncontrasting
confidence: 65%
“…The youngest child treated by LDL apheresis was 3.5 years old (8), as in our series. The most frequently used method was adsorption by DSC (4,5,8–11), but other procedures were also used: heparin‐induced lipoprotein precipitation (HELP) (7), immunoadsorption (12), direct adsorption by DALI (13), and even non‐specific methods such as plasma exchange (6). Although weekly sessions are more efficient (10), fortnightly sessions were often performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were treated only by LDL-apheresis. All patients were subjected to consecutive coronary angiography to moni-LDL oxidation and GSH content after LDL-apheresis [14][15][16][17]. The study included two types of FH patients : (1) patients receiving fortnightly LDL-apheresis treatment (ON patients ; n l 9) ; and (2) patients receiving their first LDL-apheresis treatment (OFF patients ; n l 5).…”
Section: Subjectsmentioning
confidence: 99%
“…The extracorporeal volume of plasma and the flow rate required generally restrict the use of plasmapheresis to larger children and adults, but it is possible with appropriate equipment to use plasmapheresis in smaller children. 53 Creating arteriovenous fistulae best attains reliable vascular access for weekly to fortnightly treatment schedules. Excessive shunting of blood may be a cardiovascular stress and necessitated fistula closure in one of our patients.…”
Section: Managementmentioning
confidence: 99%